Levamisole-induced vasculitis - Abdul-Karim, Raghad (Baylor Health Care System, 2013)
Levamisole-contaminated cocaine is an increasingly reported cause of a syndrome characterized by vasculitic skin lesions and immunologic abnormalities. With approximately 70% of cocaine in the United States now contaminated with levamisole, the incidence of this syndrome is likely to increase. We report two cases of this syndrome and review its clinical presentation, course, and prognosis.